EARLY CRETACEOUS RADIOLARIANS IN MANGANESE CARBONATE NODULE FROM THE BARRU AREA, SOUTH SULAWESI, INDONESIA. - Munasri Munasri (Indonesian Institute of Sciences, 2013)
Abstract The Mesozoic basement complex in South Sulawesi, Indonesia, is exposed in two areas near Bantimala and Barru, known as the Bantimala Complex and the Barru Complex. The complexes consist of metamorphic, ultramafic and sedimentary rocks. Part of these rocks was chaotically mixed to form a mélange. Early Cretaceous (Valanginian to Barremian) radiolarians were extracted from manganese carbonate nodule embeded in dark reddish shale of the Barru Complex. Previously middle Cretaceous (late Albian to early Cenomanian) radiolarian assemblage was reported found in chert and siliceous shale of the Bantimala Complex.The hemipelagic dark reddish shale with manganese carbonate nodule of the Barru Complex are considered to have been deposited in Early Cretaceous time (Valanginian to Barremian) and accreted at the subduction trench during late Early Cretaceous (Aptian) time.Based on radiolarian data, it is considered that the Barru and Bantimala Complexes were not derived from single accretionary complex as previously regarded.